2021
DOI: 10.21037/atm-21-6516
|View full text |Cite
|
Sign up to set email alerts
|

Mitosis-related gene CENP-U as a potential biomarker in malignancy

Abstract: Background: Centromere protein U (CENP-U) is a component of the kinetochore and can regulate the cell cycle as a receptor of polo-like kinase 1 (PLK1). Recent studies have partially identified the role of CENP-U in tumor progression, but the underlying mechanisms of CENP-U in tumor immunity remain obscure. Methods: We performed pan-cancer analysis to evaluate the role of CENP-U in immunity and proliferation with data from The Cancer Genome Atlas (TCGA), Cancer Cell Line Encyclopedia (CCLE) datasets, and Genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…These results suggest that CENPO plays an important immunomodulatory role and may serve as a potential immunotherapeutic relevant biomarker. Previous studies reported that the CENP family is associated with immune function [6,43], and our bioinformatics results also demonstrated that CENPO is associated with immune regulation. We then demonstrated by in vitro experiments that CENPO was highly expressed in A549 and H1299 cell lines and that the knockdown of CENPO significantly inhibited the proliferative activity, migration, and invasive ability of A549 and H1299 cells, suggesting that CENPO may affect LUAD metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…These results suggest that CENPO plays an important immunomodulatory role and may serve as a potential immunotherapeutic relevant biomarker. Previous studies reported that the CENP family is associated with immune function [6,43], and our bioinformatics results also demonstrated that CENPO is associated with immune regulation. We then demonstrated by in vitro experiments that CENPO was highly expressed in A549 and H1299 cell lines and that the knockdown of CENPO significantly inhibited the proliferative activity, migration, and invasive ability of A549 and H1299 cells, suggesting that CENPO may affect LUAD metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…These results suggest that CENPO plays an important immunomodulatory role and may serve as a potential immunotherapeutic relevant biomarker. Previous studies reported that the CENP family is associated with immune function [6,40], and our bioinformatics results also demonstrated that CENPO is associated with immune regulation. We then demonstrated by in vitro experiments that CENPO was highly expressed in A549 and H1299 cell lines and that the knockdown of CENPO signi cantly inhibited the proliferative activity, migration, and invasive ability of A549 and H1299 cells, suggesting that CENPO may affect LUAD metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…CENPs are important members of the centromere and kinetochore, which determine the separation of chromosomes during mitosis and meiosis. Many CENPs have been currently identified, including CENPA, CENPH, CENPI, and CENPU (7)(8)(9)(10)(11). Among them, CENPA plays a significant role in cancer.…”
Section: Introductionmentioning
confidence: 99%